The EU FLEGT scheme: a critical analysis of its potential for promoting effective and equitable forest governance in Africa - Dlamini, Cliff Sibusiso (Department of Public Law, 2016)
This dissertation critically considers and assesses the potential of the EU FLEGT Scheme to provide an effective and equitable legal regime for curbing illegal logging and promoting sustainable forest management (SFM) and good forest governance (GFG) in African Partner Countries. It considers a broad range of issues starting with the state of Africa's forests and the international regulatory framework for SFM. A critical review of recent studies led to a theoretical framework comprising a set of specific legal issues/themes (substantive issues) central to SFM and GFG. These were accompanied by three broad cross - cutting themes. The substantive issues are: (i) security/clarity on land tenure , ownership and use rights; (ii) stable institutional structures; (iii) clear environmental and forestry standards; (iv) effective and equitable approval processes; (v) participatory, transparent and accountable decision - making; (vi) cooperation and coordination procedures; (vii) monitoring, evaluation and reporting; (viii) effective compliance and enforcement; (ix) financial incentives; (x) equitable sharing of benefits; (xi) conflict resolution procedures; and (xii) mixture of regulatory approaches (direct regulation and voluntary mechanisms). The cross - cutting themes entail: (i) clear coherent and consistent law and policy; (ii) adherence/respect of the rule of law; and (iii) knowledge, capacity and resources. A rigorous assessment of the EU FLEGT Scheme against this theoretical framework shows that the FLEGT Voluntary Partnership Agreements (VPAs) and the EU Timber Regulation (EUTR) form a robust legal regime. The structure of FLEGT VPAs is based on the 16 Principles for FLEGT Partnership Agreements of 20 05 and the 18 key elements of FLEGT VPAs. Thus FLEGT VPAs have provided a landmark mechanism for multi - stakeholder participation in the forestry sector, and have propelled inclusivity in decision - making. Thus FLEGT VPAs are founded on international law and international trade laws. On the other hand, the EUTR is composed of a stringent Due Diligence System (DDS) and provision that emphasize legality as a cornerstone for FLEGT. In this context, legality requires the establishment of standards of legality, i. e. timber legality assurance systems and FLEGT licensing. This involves requirements for verification, guidelines for independent monitoring, and market - based legality assurance. Although the FLEGT VPAs and EUTR cover all the 15 legal themes listed above, inconsistences in national laws and sovereignty on forest resources have either hampered or slowed down effective and efficient implementation of FLEGT VPAs. Nonetheless, remarkable progress has been observed in forest governance across Partner Countries. More research is needed to ascertain the effectiveness of the EUTR and the degree of reduction in illegal logging in Partner Countries. Lastly, there are reports that that African timber producing countries have started to increase their exports to other international markets e.g. Australia, USA, China and Japan. Therefore, it is crucial that the EU collaborate with these international markets and enter into bilateral and multilateral negotiations so as to collectively deal with illegal logging and illegal timber and make a positive impact at a global scale.